Intranasal Immunization with Influenza Virus-Like Particles Containing Membrane-Anchored Cholera Toxin B or Ricin Toxin B Enhances Adaptive Immune Responses and Protection against an Antigenically Distinct Virus - Ji, Xianliang (Viruses, 2016)
Vaccination is the most effective means to prevent influenza virus infection, although current approaches are associated with suboptimal efficacy. Here, we generated virus-like particles (VLPs) composed of the hemagglutinin (HA), neuraminidase (NA) and matrix protein (M1) of A/Changchun/01/2009 (H1N1) with or without either membrane-anchored cholera toxin B (CTB) or ricin toxin B (RTB) as molecular adjuvants. The intranasal immunization of mice with VLPs containing membrane-anchored CTB or RTB elicited stronger humoral and cellular immune responses when compared to mice immunized with VLPs alone. Administration of VLPs containing CTB or RTB significantly enhanced virus-specific systemic and mucosal antibody responses, hemagglutination inhibiting antibody titers, virus neutralizing antibody titers, and the frequency of virus-specific IFN-γ and IL-4 secreting splenocytes. VLPs with and without CTB or RTB conferred complete protection against lethal challenge with a mouse-adapted homologous virus. When challenged with an antigenically distinct H1N1 virus, all mice immunized with VLPs containing CTB or RTB survived whereas mice immunized with VLPs alone showed only partial protection (80% survival). Our results suggest that membrane-anchored CTB and RTB possess strong adjuvant properties when incorporated into an intranasally-delivered influenza VLP vaccine. Chimeric influenza VLPs containing CTB or RTB may represent promising vaccine candidates for improved immunological protection against homologous and antigenically distinct influenza viruses.